Analisis Peran Hindu Rights Action Force (HINDRAF) DalamUpayaRekognisiIdentitas Diaspora India di Malaysia - Susila Wati; Syaiful Anam; Ahmad Mubarak Munir (Indonesian Journal of Global Discourse, 2021)
In the early part of 2008, a major political upset was pulled off in Malaysia when the ruling coalition, Barisan Nasional (National Front), lost its almost sixty years long-held parliamentary majority after the general elections. It is The Hindu Rights Action Force (HINDRAF) came out from a series of controversial actions perceived by the Malaysian Indian community as discriminatory such as the errant destruction of Hindu temples and the body-snatching cases of Tamil Hindus, thought to have been converted to Islam, as well as the state of poverty confronted by the Tamil Hindu community in Malaysia. The 2007 rally event had an overwhelming impact internationally, drawing attention to the plight of Malaysian Tamil Hindus. However, the aim of this study will demonstrate that by the subsequent two general Malaysian elections of 2013 and 2018, the Tamil Hindus, as represented by HINDRAF, had not achieved their goals. Enduring heavy-handed treatment by the Malaysian authorities previously and troubled by internal strife and leadership issues within HINDRAF, this movement of Tamil Hindus in Malaysia stand diluted and divided. The result showed that after the 14th general election of 2018, it seems that the leadership has also accepted a compromised position. Malay-Muslim majoritarianism remains dominant and the “New Malaysia” appears less than that heralded in the early days of the new Pakatan Harapan government. This research uses qualitative methods.